Optimisation and Validation of a High Throughput Screening Compatible Assay to Identify Inhibitors of the Plasma Membrane Calcium ATPase Pump - a Novel Therapeutic Target for Contraception and Malaria - Tamer M A Mohamed; Simon A Zakeri; Florence Baudoin; Markus Wolf; Delvac Oceandy; Elizabeth J Cartwright; Sheraz Gul; Ludwig Neyses (Frontiers Media S.A., 2013)
Purpose. ATPases, which constitute a major category of ion transporters in the human body, have a variety of significant biological and pathological roles. However, the lack of high throughput assays for ATPases has significantly limited drug discovery in this area. We have recently found that the genetic deletion of the ATP dependent calcium pump PMCA4 (plasma membrane calcium/calmodulin dependent ATPase, isoform 4) results in infertility in male mice due to a selective defect in sperm motility. In addition, recent discoveries in humans have indicated that a single nucleotide polymorphism (SNP) in the PMCA4 gene determines the susceptibility towards malaria plasmodium infection. Therefore, there is an urgent need to develop specific PMCA4 inhibitors. In the current study, we aim to optimise and validate a high throughput screening compatible assay using recombinantly expressed PMCA4 and the HTRF® Transcreener® ADP (TR-FRET) assay to screen a drug library. Methods and Results. PMCA4 membrane microsomes were prepared from HEK293 cells overexpressing PMCA4. Western blot quantification revealed nearly nine-fold increased expression of PMCA4 compared to LacZ (control virus)-infected cells. Maximal PMCA4 microsomal activity was achieved in the TR-FRET assay with 15ng/μl microsomal concentration, 30-minute pre-incubation with compounds at 37°C, and calcium buffering with 1mM EGTA providing 1μM free-calcium. Finally a dose-response curve for carboxyeosin (a non-specific PMCA inhibitor) under optimised conditions showed significant PMCA4 inhibition. Upon confirmation that the assay was suitable for high-throughput screening, we have screened the ChemBioNet small molecule library (~21,000 compounds) against the PMCA4 assay to identify those that are its apparent inhibitors. This screening yielded 1,494 primary hits. Conclusions. We have optimised the HTRF® Transcreener® ADP assay for high-throughput screening to identify PMCA4 inhibitors. The output of the screening campaign has provided preliminary chemical starting points that could be further developed to specific PMCA4 inhibitors for non-hormonal contraception or anti-malaria therapy. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.